The Impact of Working Capital Management on Corporate Performance under Financial Constraints: Evidence from Metal Industry in Finland. - Kulmala-Teiskonen, Mia (My University, 2018)
Working capital management plays an essential role in short term financing of companies’ everyday operations and has an important effect on both liquidity and profitability. It covers optimization of working capital in the value chain of the entire company, from raw materials to final products. This study investigates the impact of working capital management on corporate performance in a group of non-listed Finnish companies in the machining sector of metal industry between years 2011-2015. The study adds to the existing literature on the topic by addressing the possible non-linearity of the relationship between working capital management and company profitability. Moreover, the existence and influence of financial constraints are observed in the same context. Based on the latest research on the topic, panel data method and least squares estimation are used to test the effect of net trade cycle (NTC) as a measure of working capital management on company performance, described by P/L ratio. The presence of financial constraints is examined by classifying the companies by cash flow, size and bankruptcy risk. The empirical findings support the expectation of a non-linear relation between company performance and working capital management, pointing out that deviations from the optimal NTC either up- of downwards reduce the corporate performance, but the result is not statistically significant. Another main result of the study indicates that the optimal working capital level of the companies facing more financial constraints based on size, cost of external financing and interest coverage is lower than for the companies with lesser financial challenges. In this sample, however, the results are statistically significant only with the cost of external financing-criteria. In practice these results suggest that working capital management should be observed as one of the key factors affecting company performance.
Keywords: working capital; net trade cycle; performance; financial constraints; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|